Characterization of assistance in elderly men assisted in a mobile emergency care service - Lívia Carvalho Pereira; Alaíde Araújo Alencar; Maria do Livramento Fortes Figueiredo; Cinara Maria Feitosa Beleza (Universidad de Alicante, 2015)
The elderly population has shown a significant increase in life expectancy in recent decades, however, they remain a population susceptible to many health hazards due to the declination of their functional physiological reserves. Coupled with this fact is the absence of public policies that prioritize the effectiveness of primary care as a gateway to the Unified Health System. This audience easily aggravates its health situation, often requiring attendance by the emergency and urgent care services. The objective of the present study was to characterize the care of elderly men by mobile emergency care service - SAMU. This is a cross-sectional, descriptive, exploratory study was developed in SAMU Teresina-PI, collection the attendance records held by SAMU between September and December 2011. The results point to a demand by the SAMU by elderly people, in the evaluated months, mainly by clinical complaints. The findings reinforce the need for more primary care coverage of health strategies that promote a better quality of life, prevention and recovery of their health.